Female EFL teachers: shifting and multiple gender and language-learner identities - Rojas, María Ximena (Colombian Applied Linguistics Journal, 2012)
Gender studies have taken an important role within the academic community, and specifically in the field of second and foreign language learning. In this paper I use a Feminist Poststructuralist Discourse Analysis (FPDA) study to explore how emergent femininities construct gender identities and power relations inside the EFL classroom setting through interaction. I argue that identities are multiple and shifting according to the way individuals position and reposition themselves through discourse(s). In doing so, gender identities can be identified and related to learners’ identities in EFL contexts. I chose a Feminist Poststructuralist Discourse Analysis (FPDA) methodology (Baxter, 2003) in order to identify telling cases (Mitchell, 1984) during interactions in which, female adult students from a private university in Bogotá, Colombia make explicit the exercising of power during classroom activities, such as debates (Castañeda- Peña, 2009) and disputes (Toohey, 2001) in foreign language learning. I chose video recordings, transcripts and interviews as instruments to cope with the objectives of the study as well as to accomplish the methodological suggestions. Findings suggest the importance of being aware of the multiplicity of gender identities that may intervene when learning a language and how to deal with more egalitarian discourses and activities during classes that guarantee, to some extent, the empowerment of silent voices.